An Evaluation of Selected Economic Areas according to Similarity of Supply and Demand Shocks - Stanislav Kappel (Review of Economic Perspectives, 2015)
The Euro Area remains a well-known monetary union in the World. But the possibilities of creation of new monetary unions are discussed. It is spoken about NAFTA (Canada, Mexico and the United States) or MERCOSUR (Argentina, Brazil, Paraguay, Uruguay and Venezuela). The aim of this paper is to assess the similarity of demand and supply shocks in the countries of NAFTA and MERCOSUR, and to compare it with the countries of the Euro Area. For these aims, correlation and structural vector autoregression methods are used. Methods are based on Blanchard and Quah (1989) and Bayoumi and Eichengreen (1993). We confirm the existence of core states and periphery states in the Euro Area with some exceptions. If we compare supply and demand shocks, we find more similarity in the case of supply shocks in the countries of the Euro Area. According to the results, the countries of NAFTA are more appropriate for the creation of monetary union than the countries of MERCOSUR. The countries of NAFTA achieve high correlation coefficients of supply and demand shocks (except Mexico for supply shocks).
Keywords: 330